2020
DOI: 10.1029/2020ja028623
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Attribution of Climate Change in the Upper Atmosphere From 1950 to 2015 Simulated by WACCM‐X

Abstract: Monitoring climatic changes in the thermosphere and ionosphere and understanding their causes is important for practical purposes. To support this effort and facilitate comparisons between observations and model results, a long transient simulation with the Whole Atmosphere Community Climate Model eXtension (WACCM-X) from 1950 to 2015 was conducted. This simulation used realistic variations in solar and geomagnetic activity, main magnetic field changes, and trace gas emissions, including CO 2 , thereby includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 61 publications
2
49
0
Order By: Relevance
“…Previous studies found that CO 2 plays a dominant role in the cooling trend in the thermosphere, with very minor contributions from the other three GHGs (∼95% vs. ∼5%) (e.g., Akmaev et al, 2006;Qian et al, 2013). Cnossen (2020) employed multilinear regression analysis to a transient WACCM-X simulation from 1950 to 2015 to estimate and attribute climate change in the T-I. Spatial patterns of trends in hmF2 and NmF2 indicated a superposition of CO 2 and geomagnetic field effects, with the latter dominating trends in the region of ∼50-20°N, ∼60°W to 20°E.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies found that CO 2 plays a dominant role in the cooling trend in the thermosphere, with very minor contributions from the other three GHGs (∼95% vs. ∼5%) (e.g., Akmaev et al, 2006;Qian et al, 2013). Cnossen (2020) employed multilinear regression analysis to a transient WACCM-X simulation from 1950 to 2015 to estimate and attribute climate change in the T-I. Spatial patterns of trends in hmF2 and NmF2 indicated a superposition of CO 2 and geomagnetic field effects, with the latter dominating trends in the region of ∼50-20°N, ∼60°W to 20°E.…”
Section: Discussionmentioning
confidence: 97%
“…Cnossen (2020) employed multilinear regression analysis to a transient WACCM‐X simulation from 1950 to 2015 to estimate and attribute climate change in the T‐I. Spatial patterns of trends in hmF2 and NmF2 indicated a superposition of CO 2 and geomagnetic field effects, with the latter dominating trends in the region of ∼50–20°N, ∼60°W to 20°E.…”
Section: Discussionmentioning
confidence: 99%
“…Cnossen [10] used the WACCM-X to consider realistic variations in solar and geomagnetic activity, the Earth's magnetic field, and trace gas emissions, including CO2, for the period 1950-2015. Trends due to Earth's magnetic field secular variation were obtained through a multiple linear regression fitting to the modeled output values where solar activity and geomagnetic activity were considered through F10.7 and Kp indices.…”
Section: Modeling Using Igrfmentioning
confidence: 99%
“…Even though anthropogenic forcing seems to be the main trend driver until now, there are also other ionospheric long-term change forcings of natural origin. Among them is the secular variation of the Earth's magnetic field, which affects not only the electron density, but ionospheric conductivity, currents flowing in the ionosphere and magnetosphere, and radio wave propagation as well [8][9][10][11][12][13]. The ionosphere, as a part of the space weather environment, plays a crucial role through the modulation of the global electrodynamic circuit, its coupling to the magnetosphere and as a key medium for communication, sounding, and navigation.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 in the model is specified as a boundary condition in the lower thermosphere and is uniformly distributed horizontally, although without consideration of the spatial and temporal variability of CO 2 in the upper atmosphere. Considering the CO 2 variability, Cnossen (2020) analyzed the long‐term database of WACCM‐X using a modified regression method to examine the impact of CO 2 and geomagnetic field changes on upper atmosphere climate change. Based on a whole atmosphere model, GAIA, the CO 2 doubling effect in the upper atmosphere and the dependence of geomagnetic activity upon the CO 2 ‐driven trend have been investigated recently (Liu HX et al, 2020, 2021).…”
Section: Introductionmentioning
confidence: 99%